(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2014)
The paper introduces first Nietzsche and then Heidegger’s views on conscience and guilt. It next identifies the ways in which their stances on this issue are opposed. Finally, it argues that from a psychotherapeutic perspective, it is the Nietzschean ideas that are more likely to be fertile directions of thought for clients.